Հայկական ժողովրդական ավանդական բնակարանային համալիրների որոշ առանձնահատկությունների շուրջ (XIX դար – XX դարասկիզբ) - Նահապետյան, Ռաֆիկ (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Исследование исторических данных и имеющихся под рукой полевых этнографических материалов показывает, что в двух частях исторической Армении изначально до конца XIX в. и начала XX в. наиболее широко распространенным типом жилищного комплекса является головной дом. Это обстоятельство свидетельствует об однородности армянского населе ния с незапамятных времен. Данная форма жилища была также распространена в соседних с Арменией странах, в которых армянское население было многочисленным. In the article, the author, on the basis of historical materials and materials of field ethnographic research at hand, shows that in two parts of historical Armenia, initially before the end of the 19th century. and the beginning of the 20th century. the most widespread type of housing complex is the head house. This circumstance testifies to the homogeneity of the Armenian population since time immemorial. This form of dwelling was also widespread in the neighboring countries of Armenia, in which there was a large number of the Armenian population.
Keywords: Հայոց պատմություն